COPPER-GOLD-PALLADIUM MINERALIZATION IN ULTRABASIC ROCKS OF THE POLAR URALS - Kuznetsov S.K.; Filippov V.N.; Onishchenko S.A.; Kotel'nikov V.G. (My University, 2007)
The northern Ural region incorporates several large ultrabasic massifs (Voykar-Osa, Rai-Iz, and Syum-Keu) confined to the Polar Ural ophiolite belt. The massifs enclose chromite deposits. The ultrabasic rocks are characterized by high concentrations of refractory platinoids (PGE) of the Ru–Os–Ir composition and the subordinate role of Pt, Pd, and Rh. Laurite, erlichmanite, cuproiridsite, irarsite, ruarsite, hollingworthite, sperrylite, and other mineral phases are subordinate. Native gold, silver, copper, and iron are also found in these massifs. Recent detailed investigations of the Polar Urals have made it possible to discover a low-sulfide copper ore occurrence on the right bank of the Dzelyatyshor Creek (left tributary of the Malaya Kharamatalou River). We have detected for the first time gold and silver associated with palladium, bismuth, and tellurium in the copper ore.